2017
DOI: 10.1016/j.ijrmms.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Shear-enhanced nonlinear flow in rough-walled rock fractures

Abstract:  Channeling and eddy flow behaviors in 3D rough-walled rock fractures enhanced by shear created asperity contacts;  Nonlinear relationship between flowrates and pressure gradients in the 3D fractures;  Nondeterministic relationship between effective transmissivity and local apertures;  Limitations of simplified 2D models in modeling nonlinear flow behaviors in roughwalled fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(53 citation statements)
references
References 41 publications
3
50
0
Order By: Relevance
“…A fracture comprised of two rough-walled surfaces in the middle of the model (in blue color) was created by using a laser-scanned natural granite rock fracture surface (Koyama et al 2008;Zou et al 2015). Specifically, this fracture model was built by a numerical 'uplift' step that simply extruded up the laser-scanned surface in the vertical height direction (Z -direction) by 0.65 mm and then a 'shear' step that shifted the upper surface along the horizontal length direction (X -direction) with a displacement of 1.0 mm (Zou et al 2016a). Such steps created a numerical 3D fracture model with spatially variable apertures and several contact spots (highlighted in red in Fig.…”
Section: Fracture-matrix Systemmentioning
confidence: 99%
“…A fracture comprised of two rough-walled surfaces in the middle of the model (in blue color) was created by using a laser-scanned natural granite rock fracture surface (Koyama et al 2008;Zou et al 2015). Specifically, this fracture model was built by a numerical 'uplift' step that simply extruded up the laser-scanned surface in the vertical height direction (Z -direction) by 0.65 mm and then a 'shear' step that shifted the upper surface along the horizontal length direction (X -direction) with a displacement of 1.0 mm (Zou et al 2016a). Such steps created a numerical 3D fracture model with spatially variable apertures and several contact spots (highlighted in red in Fig.…”
Section: Fracture-matrix Systemmentioning
confidence: 99%
“…Several studies have shown that textures with heterogeneous connectivity structures can strongly impact flow channeling both in porous media (Fiori et al, ; Gotovac et al, ; Vasco et al, ; Zinn & Harvey, ) and in single fractures (Brown, ; Detwiler & Rajaram, ; Nicholl et al, ; Zou et al, , ). A few studies have investigated effects of internal fracture variability in fracture networks, with a range of results indicating minor to notable effects on transport (Cvetkovic & Frampton, ; de Dreuzy et al, ; Frampton et al, ; Makedonska et al, ; Painter, ; Zou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is typically not due to model limitations, but rather because of a lack of comprehensive suitable field information, which reflects the challenges involved in measuring fracture aperture and its variability at multiple scales for in situ field conditions. Several studies have shown that textures with heterogeneous connectivity structures can strongly impact flow channeling both in porous media (Fiori et al, 2010;Gotovac et al, 2009;Vasco et al, 2016;Zinn & Harvey, 2003) and in single fractures (Brown, 1987;Detwiler & Rajaram, 2007;Nicholl et al, 1999;Zou et al, 2015Zou et al, , 2017b. A few studies have investigated effects of internal fracture variability in fracture networks, with a range of results indicating minor to notable effects on transport de Dreuzy et al, 2012;Frampton et al, 2018;Makedonska et al, 2016;Painter, 2006;Zou et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, shear impacts on flow regimes and nonlinear flow behavior have been investigated by numerical methods and experimental investigations. The numerical simulation studies proposed that shear displacement can enhance the degree of flow nonlinearity and induce nonlinear laminar flow in rough‐walled fractures . However, the shear step is created by artificially moving one half of wall with respect to the other wall, which was not received from physically realistic laboratory test.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation studies proposed that shear displacement can enhance the degree of flow nonlinearity and induce nonlinear laminar flow in rough-walled fractures. 47,48 However, the shear step is created by artificially moving one half of wall with respect to the other wall, which was not received from physically realistic laboratory test. This leads to that the opposite response was observed for the experimental investigations.…”
Section: Introductionmentioning
confidence: 99%